2002
DOI: 10.1093/oxfordjournals.molbev.a004099
|View full text |Cite
|
Sign up to set email alerts
|

Diversifying Selection of the Tumor-Growth Promoter Angiogenin in Primate Evolution

Abstract: Diversifying selection drives the rapid differentiation of gene sequences and is one of the main forces behind adaptive evolution. Most genes known to be shaped by diversifying selection are those involved in host-pathogen or male-female interactions characterized as molecular "arms races." Here we report the unexpected detection of diversifying selection in the evolution of a tumor-growth promoter, angiogenin (ANG). A comparison among 11 primate species demonstrates that ANG has a significantly higher rate of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 56 publications
0
28
0
Order By: Relevance
“…We suggest that the connection between positive selection at the molecular level and cancer is driven by the strong, ongoing selection generated by evolutionary conflict (see also Ewald, 2000 ;Huttley et al, 2000 ;Zhang & Rosenberg, 2002). By this hypothesis, most of the cancer genes that show evidence of positive selection have been subject to antagonistic coevolution, which varies in its dynamics and strength among lineages.…”
Section: Positive Selection In the Evolution Of Cancermentioning
confidence: 83%
“…We suggest that the connection between positive selection at the molecular level and cancer is driven by the strong, ongoing selection generated by evolutionary conflict (see also Ewald, 2000 ;Huttley et al, 2000 ;Zhang & Rosenberg, 2002). By this hypothesis, most of the cancer genes that show evidence of positive selection have been subject to antagonistic coevolution, which varies in its dynamics and strength among lineages.…”
Section: Positive Selection In the Evolution Of Cancermentioning
confidence: 83%
“…Recently, a suite of genes involved in carcinogenesis have been shown to exhibit signatures of positive selection [44][45][46] and, in each case, this selection appears to involve evolutionary antagonisms, such as those seen in parent-offspring conflict, sexual conflict, sexually selected conflict or intragenomic conflict [46][47][48].…”
Section: Evolution Of Cancer Risk and Anticancer Adaptationmentioning
confidence: 99%
“…For example, cadherins, a class of homophilic self-recognition proteins involved in cell adhesion and tissue invasion in both placentation and carcinogenesis, might be prone to positively selected 'green-beard' mutations during placental development, which favor the specific allele involved but harm other alleles [52,53]. Similarly, Zhang and Rosenberg [44] suggested that the positive selection that they inferred on the ANG gene, which is instrumental in angiogenesis during placentation as well as cancer, was related to maternal-fetal conflict. Parent-offspring conflict might also [25,26].…”
Section: Evolution Of Cancer Risk and Anticancer Adaptationmentioning
confidence: 99%
“…Positive selection was also detected in the human-chimpanzee comparison of the breast and ovarian cancer susceptibility gene 1 (BRCA1) (Huttley et al, 2000). Angiogenin (ANG), a tumorgrowth promoter, appears to be positively selected in primates (Zhang and Rosenberg, 2002). Clark et al (2003) examined 7645 sets of orthologous genes from humans, chimpanzees, and mice, and found that Mendelian disease genes were positively selected more often than other genes on the human branch.…”
Section: Association Between Positive Selection and Diseasesmentioning
confidence: 99%